Un-Trumping America : a plan to make America a democracy again - Pfeiffer, Dan (Twelve, 2020)
"From the #1 New York Times bestselling author of Yes We (Still) Can and cohost of Pod Save America, a sharp political playbook for how Democrats can take on Trump, McConnell, Fox News, and the rest of the right-wing circus dominating American politics. There is nothing more important than beating Donald Trump in 2020, but defeating Trump is just the start of this timely book. Un-Trumping America offers readers three critical insights: first, Trump is not an aberration, but rather the logical extension of the modern Republican Party; second, how Democrats can defeat Trump in 2020; and third, preventing the likes of Trump from ever happening again with a plan to fix democracy. While the catalog of the president's crimes is long and growing, undoing Trumpism--the political platform of racism, authoritarianism, and plutocracy that gave rise to Trump and defines the Republican Party--is a long and continuing fight. Through a craven, cynical strategy engineered by Mitch McConnell, funded by the Kochs, and fueled by Fox News propaganda, Republicans have rigged American politics to drown out the voices of the people in favor of the powerful. Without an aggressive response that recognizes who the Republicans are and what they have done, American democracy as we know it won't survive this moment and a conservative, shrinking, mostly white minority will govern the country for decades. Un-Trumping America dismantles toxic Trumpism and offers a way forward. Dan Pfeiffer worked for nearly twenty years at the center of Democratic politics, from the campaign trail to Capitol Hill to Barack Obama's White House. But it was Trump's victory and Republicans' incessant aiding and abetting of Trumpism that has radicalized his thinking. Here, Pfeiffer urges Democrats to embrace bold solutions--from fixing the courts to abolishing the electoral college to eliminating the filibuster--in order to make America more democratic (and Democratic). Un-Trumping America is a powerful call for Democrats and progressives to get smarter, tougher, and more aggressive without becoming a paler shade of orange"--Dust jacket flap.